Human longevity : omega-3 fatty acids, bioenergetics, molecular biology, and evolution - Valentine, R. C. (Raymond Carlyle), 1936-; Valentine, David L. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Human cells are protected from the ravages of aging by defensive systems including novel mechanisms against membrane oxidation introduced in this book. The book proposes a unified concept in which aging cells faced with declining energy production by mitochondria and the relatively high cost of protecting membranes against oxidation are triggered by energy stress to activate programmed cellular death. It includes case histories illustrating the duality of polyunsaturated membranes in aging and longevity. It also explains the relationship between membrane unsaturation and longevity leading to a unified concept of aging.'--
'This book is built on the proposition that we age as our mitochondria age. We suggest a revised version of Harman's famous hypothesis featuring mitochondrial oxidative and energy stresses as the root causes of aging. It is well known that cellular death or apoptosis is triggered by energy stress or oxidative stress. There is convincing data showing that as mitochondria age mitochondrial DNA (mtDNA) accumulates mutations decreasing energy output. Protecting highly unsaturated mitochondrial membranes against oxidative stress also consumes an extraordinary amount of energy'--
Includes bibliographical references and index.
Keywords: Aging -- Genetic aspects; Mitochondria; Oxidative stress; Omega-3 fatty acids -- Health aspects; MEDICAL / Biochemistry; SCIENCE / Life Sciences / Biology / Molecular Biology; TECHNOLOGY & ENGINEERING / Food Science